Effect of chelated iron, iron filings and sulfur on vegetative, yield and fruit characteristics of strawberry (Fragaria x ananassa Duch) Cv. Cadonca - Bani, Shukri H. Salih (Sulaimani Journal for Pure and Applied Sciences, 2015)
The present study was conducted during growing season 2013-2014, to investigate the effects of chelated iron (0, 50 and 100mg Fe l-1), iron filings (0 and 10g plant-1) and agricultural sulfur (0 and 10g S plant-1) on vegetative, yield and fruit characteristics of strawberry Cadonca cultivar. The results showed that the foliar spray with chelated iron (50 and 100mg Fe l-1) and soil treatment with iron filings (10g plant-1) caused significant increases in each of leaf iron content, leaf total chlorophyll content, leaf dry matter percentage, plant yield, and fruit total soluble solids. Soil treatment with agriculture sulfur (10g S plant-1) also caused increases in each of leaf iron content, leaf total chlorophyll content, leaf dry matter percentage, plant yield, and fruit total acidity but did not reach to significant levels. The effect of interactions between each of iron filings + sulfur, iron filings +cheleted iron and sulfur + chelated iron were significant with the most of parameters. The interaction between 10g iron filings plant-1 + 10g S plant -1, 10g iron filings plant-1+100mg chelated iron l-1 and 10g S plant -1 + 100mg chelated iron l-1 significantly increased the most studied parameters. In respect of interaction of the three studied factors, the interaction of 10g iron filings plant-1 + 10g S plant-1 +100mg chelated iron l-1 was the best thrice interaction in promoting the most studied characteristics.
Keywords: Strawberry; chelated iron; iron filings; sulfur